Evaluating the relationships between the legal and illegal international wildlife trades. Issue 5 (9th May 2020) - Tittensor, Derek P.; Harfoot, Michael; McLardy, Claire; Britten, Gregory L.; Kecse‐Nagy, Katalin; Landry, Bryan; Outhwaite, Willow; Price, Becky; Sinovas, Pablo; Blanc, Julian; Burgess, Neil D.; Malsch, Kelly
Abstract: The international legal trade in wildlife can provide economic and other benefits, but when unsustainable can be a driver of population declines. This impact is magnified by the additional burden of illegal trade, yet how it covaries with legal trade remains little explored. We combined law‐enforcement time‐series of seizures of wildlife goods imported into the United States (US) and the European Union (EU) with data on reported legal trade to evaluate the evidence for any relationships. Our analysis examined 28 US and 20 EU products derived from CITES‐listed species with high volume and frequency of both reported trade and seizures. On average, seizures added 28% and 9% to US and EU reported legal trade levels respectively, and in several cases exceeded legal imports. We detected a significant but weak overall positive relationship between seizure volumes and reported trade into the US over time, but not into the EU. These results highlight the importance of maintaining long‐term records of border seizures and enforcement effort, and accounting for illegal trade where possible in non‐detriment findings. Our findings suggest a complex and nuanced temporal association between the illegal and legal wildlife trades.